Patterns of Medical and Nursing Staff Communication in Nursing Homes: Implications and Insights From Complexity Science - Colón-Emeric, Cathleen S. (2006)
Complexity science teaches that relationships among health care providers are key to our understanding of how quality care emerges. The authors sought to compare the effects of differing patterns of medicine-nursing communication on the quality of information flow, cognitive diversity, self-organization, and innovation in nursing homes. Two facilities participated in 6-month case studies using field observations, shadowing, and depth interviews. In one facility, the dominant pattern of communication was a vertical “chain of command” between care providers, characterized by thin connections and limited information exchange. This pattern limited cognitive diversity and innovation in clinical problem solving. The second facility used an open communication pattern between medical and frontline staff. The authors saw higher levels of information flow, cognitive diversity, innovation, and self-organization, although tempered by staff turnover. The patterns of communication between care providers in nursing facilities have an important impact on their ability to provide quality, innovative care.